Pemodelan Pembelajaran Problem Based Learning Berbasis Isu Bencana Untuk Guru Biologi dan IPA di Nagari Silokek, Kab. Sijunjung - Muhyiatul Fadilah; Helendra Helendra; Heffi Alberida; Rahmawati Rahmawati; Elifia Zulfa Endela; Syafira Defni; Putri Reuni (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Nagari Silokek is being developed towards the Silokek Geopark, but the topographic structure of this nagari is prone to floods and landslides. This threat must be minimized by intensively introducing disaster issues, one of which is integration into learning. The purpose of this service is to improve the professional and pedagogical competence of science / science teachers in implementing Problem Based Learning (PBL) which is stimulated by contextual content, namely disaster issues in Silokek. The method of this community service is disaster issue-based PBL modeling training and making interactive learning media to support PBL learning in the form of Kahoot and Quizziz. This activity is complemented by a visit to the biology and science learning research product stand. The results of the training evaluation questionnaire showed that all participant (100%) expressed interest in the PkM activities carried out, becoming motivated to improve the learning process in the classroom. The role of the PkM team was also maximized in providing knowledge updates for participants. The modeling designed also runs well through sharp and precise explanations of the needs of the participants.